2016
DOI: 10.1007/s40279-016-0651-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Outcome Measures of the Impact of Injury and Illness on Athlete Performance: A Systematic Review

Abstract: BackgroundSelf-reported outcome measures of athlete health, wellbeing and performance add information to that obtained from clinical measures. However valid, universally accepted outcome measures are required.ObjectiveTo determine which athlete-reported outcome measures of performance have been used to measure the impact of injury and illness on performance in sport and assess evidence to support their validity.MethodsThe authors searched Ovid MEDLINE, Ovid EMBASE, CINAHL Plus, SPORTDiscus with Full Text and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
19
0
4
Order By: Relevance
“…Of those with caries (DT ≥ 1), the median number of teeth affected was 2 (range 1-13). For those with one or more restorations (71.6%; 95% CI 66.7-76.1), the median number of teeth affected was 4 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nine of ten athletes (90.1%; 95% CI 86.5-92.9) assessed their general health as very good or good, and seven of ten (69.2%; 95% CI 64.1-73.8) assessed their oral health at this level (Tables S7,S8) Each variable was dichotomized to effect/no effect (Tables S11, S12). The presence of dental caries was associated with nonzero score for difficulty eating (P = .048).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those with caries (DT ≥ 1), the median number of teeth affected was 2 (range 1-13). For those with one or more restorations (71.6%; 95% CI 66.7-76.1), the median number of teeth affected was 4 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nine of ten athletes (90.1%; 95% CI 86.5-92.9) assessed their general health as very good or good, and seven of ten (69.2%; 95% CI 64.1-73.8) assessed their oral health at this level (Tables S7,S8) Each variable was dichotomized to effect/no effect (Tables S11, S12). The presence of dental caries was associated with nonzero score for difficulty eating (P = .048).…”
Section: Resultsmentioning
confidence: 99%
“…To limit the length of the questionnaire, we used three items, most likely to be relevant to this young, fit population, to assess impact on quality of life (difficulty eating/drinking, relaxing including sleeping and smiling, laughing or showing teeth without embarrassment) taken from the Oral Impacts on Daily Performance (OIDP) outcome measure used in the Adult Dental Health Survey for England, Wales and Northern Ireland (ADHS 2009) . We employed the Oslo Sports Trauma Research Centre (OSTRC) overuse injury questionnaire to assess impact on performance, given that a systematic review identified this measure as having greatest validity in sport.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como consequência, observa-se que os atletas, especialmente os de alto rendimento, têm sido cada vez mais exigidos em termos de desempenho. O aumento do nível de exigência gera situações que podem ser consideradas potencialmente perigosas à saúde e ao bem-estar dos atletas (3)(4)(5) .…”
Section: Introductionunclassified
“…As pesquisas sobre o cuidado e a saúde dos atletas de voleibol têm focalizado principalmente o risco de lesões e cargas excessivas de atividade física (5)(6)(7) . No entanto, revisão integrativa sobre o cuidado em saúde e enfermagem no contexto do voleibol evidenciou a necessidade de estudos sobre cuidado de forma sistêmica, para além de processos biológicos focados no trauma, estresse e desgastes orgânicos (6) .…”
Section: Introductionunclassified